Pharmacognostic characteristics, physical properties and chromatographic fingerprints of Curcuma comosa Roxb. rhizome samples collected in Thailand - Petchprayoon, Chutima; Charupant, Kornvika; Krabesri, Sirichai; Kitisripanya, Tharita; Aneklaphakij, Chaiwat; Bunsupa, Somnuk; Anantachoke, Natthinee; Satitpatipan, Veena; Chatsumpun, Nutputsorn; Sithisarn, Pongtip (Agriculture and Natural Resources, 2022)
Importance of the work: There is no monograph or specification of Curcuma comosa rhizomes in Thailand. The misuse of the wrong Curcuma species affects the safety and effectiveness of their herbal uses. Objectives: To evaluate the physical, microscopic and phytochemical characteristics of C. comosa rhizomes. Materials & Methods: Twelve C. comosa rhizome samples collected from different locations in Thailand were evaluated for physical, microscopic and phytochemical characteristics using the official methods. Results: The C. comosa rhizomes had a specific light odor and a slightly astringent taste. The important histological features of the C. comosa rhizomes were the corks, which were composed of alternating layers of rectangular cells. The cortex was composed of numerous parenchyma cells, with some containing starch granules or oleoresin. The foreign matter contents were less than 1% weight per weight (w/w), with a loss on drying of less than 11% w/w. The total ash and acid-insoluble ash contents were less than 14% weight per weight (w/w) and 3% w/w, respectively. The mean (± SD) ethanol-soluble extractive and water-soluble extractive contents were in the ranges 7.63 ± 0.16–40.66 ± 0.29% w/w and 14.07 ± 0.15–24.58 ± 0.33% w/w, respectively. The mean (± SD) swelling index was 3.54 ± 0.44. Thin layer chromatographic analysis of C. comosa rhizome samples showed specific chromatographic fingerprints. Phytochemical screening using color reaction suggested the presence of phenolic and steroid compounds. Main finding: The phytochemical profile of the C. comosa rhizome was reported along with the physical properties and the macroscopic and microscopic characteristics. These results can be utilized for the quality control of raw materials and finished products.